Efficacy and Safety of Ophthalmic Steroids in the Management of Polypoidal Choroidal Vasculopathy: A Systematic Review - Adriono GA; Triyoga IF; Kadharusman MM; Victor AA; Djatikusumo A; Yudantha AR; Hutapea MM (Clinical Ophthalmology)
Gitalisa Andayani Adriono,1,2,* Ichsan Fauzi Triyoga,3,* Marcello Mikhael Kadharusman,3,* Andi Arus Victor,1 Ari Djatikusumo,1 Anggun Rama Yudantha,1 Mario Marbungaran Hutapea1 1Department of Ophthalmology, Kirana Eye Centre - Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia; 2JEC Eye Hospitals and Clinics, Jakarta, Indonesia; 3Faculty of Medicine, University of Indonesia, Jakarta, Indonesia*These authors contributed equally to this workCorrespondence: Gitalisa Andayani Adriono, Department of Ophthalmology, Kirana Eye Centre - Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia, Kimia Street, Jakarta, 10320, Indonesia, Tel +62 811 131 660, Email gitalisa.andayani@ui.ac.idPurpose: This review aims to clarify the role of ophthalmic steroids in polypoidal choroidal vasculopathy (PCV) treatment.Methods: A systematic literature search was performed using Scopus, PubMed, MEDLINE, Cochrane, ProQuest, and manual searches. The primary outcome was changes in best-corrected visual acuity. The secondary outcomes were anatomical changes and incidence of adverse events.Results: Of the 100 articles identified, 9 studies were included: six treatment-naive studies, two anti-VEGF resistant studies, and one involving hemorrhagic retinal detachment. Triamcinolone acetonide was administered in seven studies, and dexamethasone in two. Altogether, 194 eyes received ophthalmic steroids in the form of intravitreal solution and slow-released implant. Overall, eight out of nine studies revealed visual acuity improvement from baseline to final follow-up, although only two studies reported significant results (0.33 ± 0.29 logMAR and 0.66 ± 0.28 logMAR) to final follow-up (0.16 ± 0.27 logMAR and 0.36 ± 0.31 logMAR). Adverse events were documented in six studies, with cataracts (6/96) and ocular hypertension (10/96) being the most common. Polyp regression and pigment epithelial detachment rates demonstrated a decline ranging from 50% to 100%. The maximum reduction observed in the central foveal thickness and central retinal thickness was − 131.4 μm and − 261.7 μm, respectively.Conclusion: Ophthalmic steroids may serve as an effective adjunctive treatment for PCV patients, irrespective of anti-VEGF resistance or hemorrhagic involvement, and may be considered as a potential monotherapy in resource-limited settings, with minimal side effects.Keywords: polypoidal choroidal vasculopathy, ophthalmic steroids, dexamethasone, triamcinolone acetonide